FUTSAL SEBAGAI SALAH SATU PERMAINAN ALTERNATIF UNTUK PEMBELAJARANSEPAKBOLA DALAM PENDIDIKANJASMANI - - Saryono (Jurnal Pendidikan Jasmani Indonesia, 2006)
Football is one of the oldest sports in the history. It is important in physical educationlearning because it is included in the curriculum. This sport can be modified with othersimilar sports in school activities. Futsal is one of the modification alternatives in football forthe teaching and learning in physical education. Futsal is an invasion game, played in afield by five people in a team with a relatively small ball and goal equipment. This sportrequires speed movements and it is interesting and safe. The winner is determined by thenumber of goal a team can make. Futsal have several fixed rules issued by FIFA. Theachievement of football is supported by futsal which is proven by the fact that many worldfootball players who played futsal when they are young. Therefore the support of futsaltoward football is significant. Physical education is an important subject using movementsand games as its media. Games in physical education should be designed to accommodateschools which have limited equipments and facilities. Futsal is one of the appropriatesports to be conducted in the type of school above to support the physical education teachingand learning. The rules of the games becomes a prominent feature to teach positivevalues in developing the student’s cognitive, affective and psychomotor abilities so that theobjectives of the physical education can be obtained.Keyword : futsal, alternatives, football, physical education.